Functional helicoidal model of DNA molecule with elastic nonlinearity - Y. M. Tseytlin (AIP Advances, 2013)
We constructed a functional DNA molecule model on the basis of a flexible helicoidal sensor, specifically, a pretwisted hollow nano-strip. We study in this article the helicoidal nano- sensor model with a pretwisted strip axial extension corresponding to the overstretching transition of DNA from dsDNA to ssDNA. Our model and the DNA molecule have similar geometrical and nonlinear mechanical features unlike models based on an elastic rod, accordion bellows, or an imaginary combination of “multiple soft and hard linear springs”, presented in some recent publications.